Clinical Feature of Men Who Benefit from Dose Escalation of Naftopidil for Lower Urinary Tract Symptoms: A Prospective Study - Takaki Mizusawa; Noboru Hara; Kenji Obara; Etsuko Isahaya; Yuki Nakagawa; Kota Takahashi (Advances in Urology)
Objectives. To examine the feature of men who benefit from dose escalation of naftopidil for lower urinary tract symptoms (LUTSs). Methods. Based on the IPSS, men reporting LUTS were prospectively studied using 50 mg/day of naftopidil for the first 4 weeks; satisfied patients continued its 50 mg/day (𝑛=11), and those reporting unsatisfactory improvement received its 75 mg/day (𝑛=35) for the next 4 weeks. Results. The 75 mg group showed improvement in the total IPSS and QOL score in a dose-dependent manner (at 4 weeks: 𝑃<.001, at 4 weeks versus 8 weeks: 𝑃<.05). In the 50 mg group, both scores reduced at 4 weeks, thereafter unchanged. The baseline slow stream score alone was higher in the 75 mg group (𝑃=.013). The rate of change in the QOL score during the initial 4 weeks (ΔQOL) and Δnocturia was smaller in the 75 mg group (𝑃<.05). Conclusions. Men with high slow stream score and unsatisfactory improvement in nocturia may benefit from dose escalation of naftopidil.